Density-Functional Tight-Binding for Platinum Clusters and Bulk: Electronic vs Repulsive Parameters. (2019) - Lee, Ka Hung; Vuong, Van Quan; Fung, Victor; Jiang, De-en; Irle, Stephan
ABSTRACT: We present a general purpose Pt-Pt density-functional tight-binding (DFTB) parameter for Pt clusters as well as bulk, using a genetic algorithm (GA) to automatize the parameterization effort. First we quantify the improvement possible by only optimizing the repulsive potential alone, and second we investigate the effect of improving the electronic parameter as well. During both parameterization efforts we employed our own training set and test sets, with one set containing ∼20, 000 spin-polarized DFT structures. We analyze the performance of our two DFTB Pt-Pt parameter sets against density functional theory (DFT) as well as an earlier DFTB Pt-Pt parameters. Our study sheds light on the role of both repulsive and electronic parameters with regards to DFTB performance.